2019
DOI: 10.1111/acer.14014
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Ethanol Intake Produces Subregion‐Specific Neuroadaptations in Striatal and Cortical Areas of Wistar Rats

Abstract: BackgroundAddiction has been conceptualized as a shift from controlled recreational use toward compulsive and habitual drug‐taking behavior. Although the brain reward system is vital for alcohol reward and reinforcement, other neuronal circuits may be involved in controlling long‐term alcohol‐seeking and drug‐taking behaviors. The aim of this study was to outline alcohol‐induced neuroplasticity in defined cortical and striatal subregions, previously implicated in alcohol use disorder.MethodsMale Wistar rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Our Syt1 KD resulted in depressed evoked potentials within the PL. Field potentials in the PL are primarily glutamatergic and mediated through AMPA receptor activation, as they are rapidly blocked by the AMPA/kainate-antagonist CNQX (35). Thus, our findings suggest that glutamatergic neurotransmission within the PL was reduced by the Syt1 KD and, by extension, is reduced in this region by alcohol dependence.…”
Section: Discussionmentioning
confidence: 54%
“…Our Syt1 KD resulted in depressed evoked potentials within the PL. Field potentials in the PL are primarily glutamatergic and mediated through AMPA receptor activation, as they are rapidly blocked by the AMPA/kainate-antagonist CNQX (35). Thus, our findings suggest that glutamatergic neurotransmission within the PL was reduced by the Syt1 KD and, by extension, is reduced in this region by alcohol dependence.…”
Section: Discussionmentioning
confidence: 54%
“…As opposed to DLS, acute EtOH potentiates GABAergic activity in the DMS by increasing mIPSC frequency; moreover, a history of EtOH drinking alters the acute alcohol effects on GABAergic transmission, inducing a decrease of mIPSC frequency rather than an increase [35]. Long-term voluntary EtOH consumption results in an increase of fEPSPs amplitude; while the decrease in evoked potentials observed in the DLS is short-lasting, the enhanced excitability in the DMS is not restored by abstinence, suggesting a long-lasting effect [36].…”
Section: Dorsomedial Striatummentioning
confidence: 95%
“…Interestingly, acute EtOH exerts different effects on mice with a previous history of alcohol intake, compared to those exposed for the first time: in fact, acute EtOH no longer inhibits mIPSC frequency in EtOH drinking mice [ 35 ]. Also, long‐term voluntary EtOH consumption exerts opposing effects on synaptic transmission in the two striatal subregions: in the DLS, it induces a depression of field excitatory postsynaptic potentials (fEPSPs) amplitude [ 36 ]. In a recent study, Patton and Colleagues demonstrated that, in the DLS, acute EtOH depresses the inhibitory MSN‐ and FSI‐MSN synapses, and the effect persisted for 15 min following the end of EtOH application, suggesting to consider it a form of EtOH‐LTD.…”
Section: Effects On Striatal Synaptic Transmission and Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…More notable is that months of EtOH consumption also leads to reduced GABAergic neurotransmission in the dorsal striatum [21]. Furthermore, the increased synaptic transmission observed after months of EtOH consumption in the dorsomedial striatum is not restored by abstinence, indicating that these effects are long-lasting [22]. Taken together, these studies demonstrate that the effects of EtOH (acute and in vivo) and washout/withdrawal from EtOH on synaptic transmission and synaptic plasticity in male rodents in the dorsal striatum are multifaceted, and bidirectional in the case of the dorsomedial striatum [14,17].…”
Section: Introductionmentioning
confidence: 99%